Population pharmacokinetics of pomalidomide in patients with relapsed or refractory multiple myeloma with various degrees of impaired renal function - Li Y; Wang X; O'Mara E; Dimopoulos MA; Sonneveld P; Weisel KC; Matous J; Siegel DS; Shah JJ; Kueenburg E; Sternas L; Cavanaugh C; et al. (Dove Medical Press, 2017)
Yan Li,1 Xiaomin Wang,2 Edward O’Mara,1 Meletios A Dimopoulos,3 Pieter Sonneveld,4 Katja C Weisel,5 Jeffrey Matous,6 David S Siegel,7 Jatin J Shah,8 Elisabeth Kueenburg,9 Lars Sternas,9 Chloe Cavanaugh,9 Mohamed Zaki,9 Maria Palmisano,1 Simon Zhou1 1Translational Development and Clinical Pharmacology, Celgene Corporation, Summit, NJ, USA; 2Non-Clinical Development and Drug Metabolism and Pharmacokinetics, Celgene Corporation, Summit, NJ, USA; 3Department of Clinical Therapeutics, National and Kapodistrian University of Athens, Athens, Greece; 4Department of Hematology, Erasmus MC Cancer Institute, Rotterdam, the Netherlands; 5Department of Hematology, University Hospital Tübingen, Tübingen, Germany; 6Department of Hematology/Oncology, Colorado Blood Cancer Institute, Denver, CO, USA; 7Myeloma Division, John Theurer Cancer Center, Hackensack University Medical Center, Hackensack, NJ, USA; 8Department of Lymphoma/Myeloma, Division of Cancer Medicine, MD Anderson Cancer Center, Houston, TX, USA; 9Global Clinical R&D, Celgene Corporation, Summit, NJ, USA Abstract: Pomalidomide is an immunomodulatory drug for treatment of relapsed or refractory multiple myeloma (rrMM) in patients who often have comorbid renal conditions. To assess the impact of renal impairment on pomalidomide exposure, a population pharmacokinetics (PPK) model of pomalidomide in rrMM patients with various degrees of impaired renal function was developed. Intensive and sparse pomalidomide concentration data collected from two clinical studies in rrMM patients with normal renal function, moderately impaired renal function, severely impaired renal function not requiring dialysis, and with severely impaired renal function requiring dialysis were pooled over the dose range of 2 to 4 mg, to assess specifically the influence of the impaired renal function as a categorical variable and a continuous variable on pomalidomide clearance and plasma exposure. In addition, pomalidomide concentration data collected on dialysis days from both the withdrawal (arterial) side and from the returning (venous) side of the dialyzer, from rrMM patients with severely impaired renal function requiring dialysis, were used to assess the extent to which dialysis contributes to the removal of pomalidomide from blood circulation. PPK analyses demonstrated that moderate to severe renal impairment not requiring dialysis has no influence on pomalidomide clearance or plasma exposure, as compared to those patients with normal renal function, while pomalidomide exposure increased approximately 35% in patients with severe renal impairment requiring dialysis on nondialysis days. In addition, dialysis increased total body pomalidomide clearance from 5 L/h to 12 L/h, indicating that dialysis will significantly remove pomalidomide from the blood circulation. Thus, pomalidomide should be administered post-dialysis on the days of dialysis. Keywords: hemodialysis, pomalidomide, population pharmacokinetics, renal impairment